2000
DOI: 10.1080/00207540050031832
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the manufacturability of machined parts and their setup plans

Abstract: Design-for-manufacturability is an approach that requires product designers to consider the manufacturing issues of a product concurrently with the geometrical and design aspects. This paper presents a manufacturability evaluation methodology that incorporates design, machining and work-holding issues. The evaluation is carried out in two parts. The ® rst part is related to the machinability of the features of the part, whereas the second part is concerned about the ® xturability of the part with regards to it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 7 publications
0
13
0
Order By: Relevance
“…Analytical hierarchy process is a structured methodology for analyzing complex decisions and finding the best alternative solution. Ong et al [34], [35] demonstrated the analytical hierarchy process-based manufacturability analysis system that estimates manufacturability index, which is the indicator of the relative ease of manufacturing, based on the different weights of the features relevant to manufacturability. Compared to the other methods, neural network-based method is a relatively recent technique that utilizes an artificial neural network to approximate complex non-linear relations.…”
Section: Traditional Manufacturability Analysis and Its Limitationmentioning
confidence: 99%
“…Analytical hierarchy process is a structured methodology for analyzing complex decisions and finding the best alternative solution. Ong et al [34], [35] demonstrated the analytical hierarchy process-based manufacturability analysis system that estimates manufacturability index, which is the indicator of the relative ease of manufacturing, based on the different weights of the features relevant to manufacturability. Compared to the other methods, neural network-based method is a relatively recent technique that utilizes an artificial neural network to approximate complex non-linear relations.…”
Section: Traditional Manufacturability Analysis and Its Limitationmentioning
confidence: 99%
“…The AHP is a mathematical based decision making technique that allows both qualitative and quantitative aspects to be taken into account when making decisions (Ong 2000;Ong 2003). It not only helps the decision makers to choose the best alternative, but also provides a clear rationale for the choice of AHP by developing and assigning priorities of criteria to judge them (Saaty 2001).…”
Section: A Approach Of Expert System Modellingmentioning
confidence: 99%
“…Work in the direction of the simultaneous consideration of machining process output variables using mathematical models has been reported by a few researchers [27][28][29][30]. However, there is need for a simple, systematic, logical, easy and convenient procedure which affords industry with an efficient and effective means to evaluate the machinability of work materials.…”
Section: Introductionmentioning
confidence: 99%